Models for Sustainable Framework in Luxury Fashion Luxury and Models - Muthu, Subramanian Senthilkannan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book highlights the models developed to create a sustainable framework suitable for luxury in the textile sector and the innovative attempts in the luxury fashion and fabrics industry. The three chapters in this book discuss these issues by means of case studies and the future of such models.
Eco-conspicuous vs Eco-conscious consumption: Co-creating a new definition of luxury and fashion -- Innovation & Sustainability in the Luxury Fashion & Fabrics Industry -- The Sustainable Model: Designing within a sustainable framework.
Keywords: Manufactures; Sustainability; Business logistics; Industrial engineering; Production engineering; Machines, Tools, Processes; Sustainability; Supply Chain Management; Industrial and Production Engineering